A review of the fernane-type triterpenoids as anti-fungal drugs - Chun-Yue Liu; Chun-Yue Liu; Lu Zhang; Si-Xuan Liu; Yong-Fu Lu; Chang Li; Yue-Hu Pei (Frontiers Media S.A., 2024)
Human fungal pathogens could cause a broad plethora of infections in both the immunocompetent and immunocompromised host. Fungal infections have become important causes of morbidity and mortality in recent years, the current arsenal of anti-fungal therapies was restricted. Ibrexafungerp was a novel, highly bioavailable glucan synthase inhibitor formulated for both intravenous and oral administration being developed by Scynexis; it was also the first novel anti-fungal drug class approved in more than 20 years. Ibrexafungerp was one semi-synthetic derivative of enfumafungin, a natural product isolated from fungi. This review reported the discovery of enfumafungin and ibrexafungerp, their anti-fungal mechanism, summed up 63 fernane-type triterpenoids from natural products, including 49 from plants, 9 from fungi and 5 from lichen. In addition, the review summarized the progress of enzymes responsible for the biosynthesis of type II fernane triterpenoid (enfumafungin skeleton) and type I fernane triterpenoid (polytolypin skeleton). The good example kept our confidence up for searching for new leading compounds and discovering drugs from fungi.